STRUKTUR ANALITIK SISTEMATIK (SAS): JEMBATAN MENUJU KEMAMPUAN MENULIS YANG TERSTRUKTUR BAGI SISWA PEMULA SEKOLAH DASAR - Efendi, Rinja; Sari, Nur Nilam; Safitri, Rahmalia; Habibah; Bulan Gerhana, Ajeng Nur; Wandira, Aida; Gustina, Ayu; Sahrani, Salsabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The lack of basic writing skills in elementary school students is often caused by teaching methods that are too theory-oriented and do not provide a useful practical context. This study aims to test the effectiveness of the Systematic Analytical Structure (SAS) Technique as a tool in improving the quality of neat writing in early grade students. The approach used is a literature review through data analysis from various accredited journals and pedagogical guidebooks. The results of the study indicate that the SAS technique, which starts from complete sentences, then breaks them down into analytical elements (words, syllables, letters), and re-arranges them in a structured manner, greatly helps students understand language structure in a logical manner. The study concludes that the SAS technique is very effective in accelerating the process of learning to write because it is in accordance with the stages of children's cognitive development based on Gestalt psychology theory. This approach not only improves writing accuracy but also forms systematic thinking patterns in students from an early age.